Polycystic Diseases in Visceral Organs - Shakila Abdul-Majeed; Surya M. Nauli (Obstetrics and Gynecology International)
Primary cilia are nonmotile, microtubule-based, antenna-like organelles projecting from the apical surface of most mammalian cells. Elegant studies have established the importance of ciliary structure and function in signal transduction and the sensory roles of cilia in maintaining healthy cellular state. In particular, dysfunctional cilia have been implicated in a large number of diseases mainly characterized by the presence of fluid-filled cysts in various organs. Aside from polycystic kidney disease (PKD), however, the roles of cilia in polycystic liver disease (PLD), polycystic pancreas disease (PPD), and polycystic ovarian syndrome (PCOS) are still very vague. In addition, although gender and sex hormones are known to regulate cyst formation, their roles in regulating physiological functions of cilia need to be further explored.